The leadership of the school principal in realizing independent learning - Mika Setiawati; Zainal Arifin; Ilham Defirono (Yayasan Azhar Amanaa Yogyakarta, 2023)
The leadership of the school principal has an important role and position for achieving educational goals. Principal leadership is a very important skill for principals who want to be successful through regular learning and training, such as using technology, books, or other means. This research aims to determine the role of school principal leadership in realizing independent learning. Apart from that, to find out the principal's leadership towards the success of educational goals and to observe the principal's leadership in creating independent learning. The results of the study show that; The school principal as a leader determines the direction of policy and the achievement of educational goals in the school, and the leadership of the school principal has an important role and position in the school's achievement, namely realizing freedom of learning. Freedom to learn is a program initiated by Nadiem Makarim, Minister of Education, Culture, Research and Technology, to produce superior people with a Pancasila student profile. The goal is to create students who are faithful and devout, independent, critical, creative, cooperative.